Circulating endocan and preeclampsia: a meta-analysis. Issue 1 (7th January 2020) - Lan, Xia; Liu, Zhaoming
Abstract: Background: Endocan, a novel protein involved in inflammation and endothelial dysfunction, has been suggested to be related to preeclampsia, although the results of previous studies were not consistent. The aim of the study was to evaluate the potential difference of circulating endocan in women with preeclampsia and those with normal pregnancy. Methods: Matched case–control studies evaluating the difference of circulating endocan between women with preeclampsia and those with normal pregnancy were identified via systematic search of PubMed and Embase databases. A random-effect model or a fixed-effect model was used to pool the results according to the heterogeneity. Subgroup analysis was performed to evaluate whether the timing of preeclampsia onset affected the outcome. Results: Overall, eight matched case–control studies, including 451 women with preeclampsia and 442 women with normal pregnancy were included. Significant heterogeneity was detected among the included studies ( P for Cochrane's Q test = 0.006, I 2 = 65%). Meta-analysis with a random-effect model showed that women with preeclampsia had significantly higher circulating level of endocan compared with women with normal pregnancy (standardized mean difference = 0.37, 95% confidence interval: 0.13–0.62, P = 0.003). Subsequent subgroup analyses showed that the difference of circulating endocan between women with early onset preeclampsia and those with normal pregnancy was not statistically different from that between women with late-onset preeclampsia and those with normal pregnancy ( P for subgroup difference = 0.81). Conclusions: Women with preeclampsia have higher circulating endocan than those with normal pregnancy.